2021
DOI: 10.1002/cmdc.202000862
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Alternative Chemotherapy Options for Leishmaniasis through Computational Studies of Asteraceae

Abstract: Leishmaniasis is a complex disease caused by over 20Leishmania species that primarily affects populations with poor socioeconomic conditions. Currently available drugs for treating leishmaniasis include amphotericin B, paromomycin, and pentavalent antimonials, which have been associated with several limitations, such as low efficacy, the development of drug resistance, and high toxicity. Natural products are an interesting source of new drug candidates. The Asteraceae family includes more than 23 000 species w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 107 publications
(131 reference statements)
0
3
0
Order By: Relevance
“…Computational studies using natural products have been reported in the continuous search for new leishmanicidal drugs or lead compounds. In particular, machine learning and molecular docking calculations have been used to identify new structures with potential anti- Leishmania activities, based on secondary metabolites found in Asteraceae species [ 17 , 18 ], especially sesquiterpenoids [ 19 , 20 ], triterpenes [ 21 ], and phytosterols [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Computational studies using natural products have been reported in the continuous search for new leishmanicidal drugs or lead compounds. In particular, machine learning and molecular docking calculations have been used to identify new structures with potential anti- Leishmania activities, based on secondary metabolites found in Asteraceae species [ 17 , 18 ], especially sesquiterpenoids [ 19 , 20 ], triterpenes [ 21 ], and phytosterols [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…AI in anti-leishmanial drug discovery is still an emerging field and at an early phase that certainly requires extensive exploration at various levels such as predicting the protein structure, studying the interaction with inhibitors, projecting the favorable structure-activity relationship, mining the possible pharmacological features, suggesting the facile chemical synthesis processes, modeling the future cost analysis for actual drug discoveries, prediction of clinical trial failure, listing the adverse effects of the future drug, suggesting post-treatment prognosis situations, and advising of alternative medical treatments. AI in leishmaniasis research has contributed to critical aspects including infection diagnosis from microscopic images, peptide-fingerprints-based prediction and modeling of enzyme classes, pyruvate kinase inhibitors designing, prognosis features of unresponsive patients, and alternative chemotherapy prediction [56][57][58][59][60].…”
Section: Emergence Of Artificial Intelligence (Ai) In Anti-leishmania...mentioning
confidence: 99%
“…Of these, nine research articles, ten reviews, and one editorial from 18 sources, the journal Current Topics in Medicinal Chemistry was the only one that submitted more than one document (three documents). Finally, all the documents found, after excluding the repeated ones, were as follows: [4,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. After reading the abstracts, the articles presented in Table 1 were selected.…”
Section: Wos Analysis (Web Of Science Core Collection)mentioning
confidence: 99%